Reciprocal Dynamics: How Ad-views and Ad-shares Reinforce Each Other - Choi, Chang-Won (Journal of Digital Marketing and Communication, 2025)
This study explores the reciprocal relationship between ad-viewing and ad-sharing in online video advertising and examines the moderating role of total likes. Drawing on two-step flow and social influence theories, it is hypothesized that daily ad-views drives daily ad-shares by reaching influencers, while daily ad-shares enhance daily ad-views through social and informational cues. Granger causality analysis of 392 YouTube advertisements reveals varying causal patterns, including reciprocal and unidirectional effects (ad-views → ad-shares and ad-shares → ad-views), with total likes amplifying these dynamics. These findings provide theoretical insights into viral advertising and practical implications.